Tetrandrine alleviates oxaliplatin-induced mechanical allodynia via modulation of inflammation-related genes - Zhang, Zhi-Ling; Wu, Zi-Yang; Liu, Feng-Yu; Hang-YuChen,; Zhai, Suo-Di (Frontiers in Molecular Neuroscience, 2024)
Oxaliplatin, a platinum-based chemotherapy drug, causes neuropathic pain, yet effective pharmacological treatments are lacking. Previously, we showed that tetrandrine (TET), with anti-inflammatory properties, reduces mechanical allodynia in nerve-injured mice. This study explores the effect of TET on oxaliplatin-induced mechanical allodynia and gene changes in mice. Male C57BL/6J mice received oxaliplatin intraperitoneally to induce mechanical allodynia. Post-treatment with TET or vehicle, the mechanical withdrawal threshold (WMT) was assessed using von Frey filaments. TET alleviated oxaliplatin-induced mechanical allodynia. RNA sequencing identified 365 differentially expressed genes (DEGs) in the Control vs. Oxaliplatin group and 229 DEGs in the Oxaliplatin vs. TET group. Pearson correlation analysis of co-regulated DEGs and inflammation-related genes (IRGs) revealed 104 co-regulated inflammation-related genes (Co-IRGs) (|cor| > 0.8, P < 0.01). The top 30 genes in the PPI network were identified. Arg2, Cxcl12, H2-Q6, Kdr, and Nfkbia were highlighted based on ROC analysis. Subsequently, Arg2, Cxcl12, Kdr, and Nfkbia were further verified by qRCR. Immune infiltration analysis indicated increased follicular CD4 T cell infiltration in oxaliplatin-treated mice, reduced by TET. Molecular docking showed strong binding affinity between TET and proteins encoded by Arg2, Cxcl12, Kdr, and Nfkbia. In summary, TET may alleviate oxaliplatin-induced peripheral neuropathy in clinical conditions.